2018
DOI: 10.1021/acs.jpcc.8b08912
|View full text |Cite
|
Sign up to set email alerts
|

Density Wave State in New α-Type Organic Conductor, α-(BEDT-TTF)2MHg(XCN)4 (M = NH4, X = Se): A Key Material for Universal Phase Diagram of X = S and X = Se Systems

Abstract: A family of organic conductors, α-(BEDT-TTF) 2 MHg(SCN) 4 , is known to show the density wave (DW) state for M = Tl, K, and Rb salts, or the superconducting (SC) state for M = NH 4 salt at low temperatures. In contrast, α-(BEDT-TTF) 2 MHg(SeCN) 4 shows no phase transition and retains its metallic characteristics down to low temperatures. Since no α-(BEDT-TTF) 2 MHg(SeCN) 4 salt shows the DW or SC states, it was unclear whether the system of α-(BEDT-TTF) 2 MHg(SeCN) 4 could be understood by the same phase diagr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 26 publications
0
3
0
Order By: Relevance
“…2 D-NMR measurements suggested a change in motion of NH + 4 at 130 K and an orderdisorder like transition in the anion layer at 25-40 K [33]. However, the spin susceptibility of NH 4 (SeCN) indicated that the motion of NH + 4 had no effect on its electronic properties [25]. A detailed study of NH + 4 in NH 4 (SCN) and NH 4 (SeCN) is required to reveal its effect on electronic properties.…”
Section: The Anomaly At T *mentioning
confidence: 97%
See 2 more Smart Citations
“…2 D-NMR measurements suggested a change in motion of NH + 4 at 130 K and an orderdisorder like transition in the anion layer at 25-40 K [33]. However, the spin susceptibility of NH 4 (SeCN) indicated that the motion of NH + 4 had no effect on its electronic properties [25]. A detailed study of NH + 4 in NH 4 (SCN) and NH 4 (SeCN) is required to reveal its effect on electronic properties.…”
Section: The Anomaly At T *mentioning
confidence: 97%
“…Chemical pressure may be more suitable to systematic NMR analyses. Recently, NH 4 (SeCN) was found to be in the DW state and to link the X = S system to the X = Se system [25]. In comparison, Tl(SeCN) was found to be in a simple metallic phase without a DW anomaly [26].…”
Section: Verticalmentioning
confidence: 99%
See 1 more Smart Citation